2012
DOI: 10.1097/pcc.0b013e318238b40d
|View full text |Cite
|
Sign up to set email alerts
|

Neurally triggered breaths have reduced response time, work of breathing, and asynchrony compared with pneumatically triggered breaths in a recovering animal model of lung injury

Abstract: Neurally triggered breaths have reduced asynchrony, trigger delay, and pressure time product, which may indicate reduced work of breathing associated with less effort to trigger the ventilator and faster response to effort. Further study is required to demonstrate if these differences will lead to decreased days of ventilation and less use of sedation in patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 15 publications
2
12
0
Order By: Relevance
“…Reductions in these asynchronies seems to be less important in other studies compared to reductions in the three main asynchronies . Flow asynchronies, defined as a mismatch between the ventilator flow and the patient flow were reported in animals during NAVA . We did not analyze this type of asynchrony in our study.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Reductions in these asynchronies seems to be less important in other studies compared to reductions in the three main asynchronies . Flow asynchronies, defined as a mismatch between the ventilator flow and the patient flow were reported in animals during NAVA . We did not analyze this type of asynchrony in our study.…”
Section: Discussionmentioning
confidence: 91%
“…13,15,17 Flow asynchronies, defined as a mismatch between the ventilator flow and the patient flow were reported in animals during NAVA. 30 We did not analyze this type of asynchrony in our study.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In a recent animal study performed in young pigs recovering from lung injury, we found that when animals were healthy, the incidence of asynchrony occurred in 8 % of pneumatically triggered inflation (Heulitt 2012). When inflation were triggered via a neural signal from an EMG signal from the diaphragm, asynchrony was still low at 6 % of inflation.…”
Section: Education Aimsmentioning
confidence: 96%